Mortality and causes of death in a Swedish series of systemic sclerosis patients. Issue 11 (1st November 1998) - Hesselstrand, Roger; Scheja, Agneta; Åkesson, Anita
Abstract : OBJECTIVES: To analyse survival rates and the causes of death in a systemic sclerosis (SSc) population, and to evaluate the occurrence of fatal malignant neoplasms and their possible association with oral cyclophosphamide (CYC) treatment. METHODS: Survival was calculated for 249 SSc patients followed up for up to 13 years. Mean (SD) follow up was 5.8 (4.2) years. The 49 deceased patients were subdivided according to causes of death and its relation to SSc. Fatal malignancies in CYC treated patients were compared with those occurring in non-CYC treated patients. RESULTS: The overall 5 and 10 year survival rates were 86% and 69% respectively. There was a 4.6-fold increased risk of death, as compared with the general population. Prognosis was worse in the diffuse cutaneous involvement (dSSc) and male subgroups than in the limited cutaneous involvement (lSSc) and female subgroups. Of the 49 deaths, 24 were attributable to pulmonary complications such as pulmonary fibrosis, pulmonary hypertension, pneumonia or pulmonary malignancy. Treatment with oral CYC did not increase the risk of dying of cancer. CONCLUSIONS: Mortality is increased both in the SSc population as a whole and in its different subsets (dSSc and lSSc). Prognosis is worst among male patients with dSSc. However, the 5 year survival rate was better than those reported from earlier studies. Most patients die of cardiopulmonary disease. Five of seven fatal lung cancers were adenocarcinomas, possibly caused by chronic inflammatory disease of the lung. In this study, CYC treatment was not associated with an increased incidence of fatal malignant neoplasms.